(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2007)
The paper elucidates results of bryoflora study in the nature reserve «Medobory». In general 132 species of 28 families and 71 genera are found. The list includes 4 species of liverworts and 128 species of mosses, information about species distribution, life forms and also taxonomic comments for selected species. Rare and interesting species in the Reserve are: Brachythecium reflexum, B. starkei, Cirriphyllum crassinervium, Ditrichum flexicaule, Fissidens exilis, F. pusillus, Funaria muehlenbergii, Plagiothecium latebricola, Platydictya confervoides, Rhodobryum ontariense, Tortula canescens.